Synthesis, characterization, and mechanistic insights into the enhanced anti-inflammatory activity of baicalin butyl ester via the PI3K-AKT pathway - Du, Hongxu; Li, Zhangxun; Su, Lijuan; He, Zhengke; Tan, Xiaoyan; Hou, Fengzhi; He, Tanjie; Pan, Yu; Xu, Shuang; Cao, Liting; Dong, Shiqi; Ma, Yue (Frontiers in Pharmacology, 2024)
Objective: To investigate the anti-inflammatory activity and mechanism of Baicalin derivative (Baicalin butyl ester, BE). Methods: BE was synthesized and identified using UV-Vis spectroscopy, FT-IR spectroscopy, mass spectrometry (MS) and high-performance liquid chromatography (HPLC) methods. Its anti-inflammatory potential was explored by an in vitro inflammation model. Network pharmacology was employed to predict the anti-inflammatory targets of BE, construct protein-protein interaction (PPI) networks, and analysis topological features and KEGG pathway enrichment. Additionally, molecular docking was conducted to evaluate the binding affinity between BE and its core targets. qRT-PCR analysis was conducted to validate the network pharmacology results. The organizational efficiency was further evaluated through octanol-water partition coefficient and transmembrane activity analysis. Results: UV-Vis, FT-IR, MS, and HPLC analyses confirmed the successfully synthesis of BE with a high purity of 93.75%. In vitro anti-inflammatory research showed that BE could more effectively suppress the expression of NO, COX-2, IL-6, IL-1β, and iNOS. Network pharmacology and in vitro experiments validated that BE's anti-inflammatory effects was mediated through the suppression of SRC, HSP90AA1, PIK3CA, JAK2, AKT1, and NF-κB via PI3K-AKT pathway.Molecular docking results revealed that the binding affinities of BA to the core targets were lower than those of BE. The Log P value of BE (1.7) was markedly higher than that of BA (-0.5). Furthermore, BE accumulated in cells at a level approximately 200 times greater than BA. Conclusion: BE exhibits stronger anti-inflammatory activity relative to BA, possibly attributed to its better lipid solubility and cellular penetration capabilities. The anti-inflammatory mechanism of BE may be mediated through the PI3K-AKT pathway.